Purification of polynucleotide phosphorylase by affinity chromatography and some properties of the purified enzymes - Smith, John C. (1974)
A method is described for the preparation of p-aminophenyl oligo(dT)-Sepharose. This matrix has been used for the purification of polynucleotide phosphorylase from both E.coli and B.stearothermophilus. The effects of temperature and pH on the binding of the different enzymes to the matrix have been investigated. B.stearothermophilus isolated by affinity chromatography may be useful in selectively removing the polyA tract on the 3′-end of mRNA's.